Anti-tumor and anti-metastatic effects of RRx-001 on hepatocellular carcinoma: mechanisms of action and therapeutic potential - Yan, Guohong; Zhao, Shuqi; Chen, Meifeng; Mo, Shutian; Huang, Hailian; Liao, Yuan; Lu, Ziyan; Liang, Jiaming; Wei, Shuxin; Han, Chuangye; Ye, Xinping (Frontiers in Pharmacology, 2024)
Background 1-Bromoacetyl-3,3-dinitroazetidine (RRx-001) has potent antitumor effects, indicating its promising therapeutic potential against various cancers. This research investigates RRx-001 activity against hepatocellular carcinoma (HCC) and elucidates its underlying mechanisms. Methods Huh7, Hepa1-6, and MHCC97H cells were cultured and treated with varying RRx-001 concentrations for 24, 48, and 72 h. Cell viability was assessed using cell counting kit-8. The cells were divided into control and RRx-001 treatment groups at 0.5 × IC50, 1.0 × IC50, and 2.0 × IC50 concentrations for each cell line. Migration and invasion were evaluated using scratch and Transwell assays, and apoptosis was examined by apoptosis assays. RNA sequencing was performed on the Huh7 cells treated with RRx-001 for 24 h to identify differential gene expression. CD47 and TP53 protein levels were measured by Western blot. A xenograft mouse model was utilized to evaluate the effect of RRx-001 on HCC. Results RRx-001 inhibits HCC cell viability, migration, and invasion while inducing apoptosis, These effects are potentially mediated by the downregulation of CD47 and the upregulation of TP53, both of which modulate key signaling pathways. In vivo experiments demonstrated that RRx-001 effectively inhibits tumor growth. Conclusion RRx-001 reduces the viability of HCC cells and induces apoptosis. This effect may be due to the downregulation of CD47 expression and the alteration of the TP53 protein regulatory pathway.